Perception of IAINU Kebumen Students on the Use of Artificial Intelligence (AI) in Pancasila Learning - Muzayanah, Sefiyani; Makfiyah, Rofi; Khoerunisa, Siti; Sofa, Nofi Maulana; Kholisoh, Zidni; Fauziah, Siti Holifatul; Subekti, Septiani; Arianto, Rahman Thooriq; Fatimah, Siti (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to examine students’ perception of artificial intelligence (AI) in learning Pancasila courses using quantitative methods. This quantitative approach uses a type of survey, with the population of all active students of IAINU Kebumen semesters 1, 3, and 5. The data collection instrument in this study uses a questionnaire with a likert scale that contains four alternative answer options, namely Strongly Agree, Agree, Disagree, Strongly Disagree. In the digital era, (Artificial Intelligence / AI) has become an important tool in education, including in teaching Pancasila values. Through a survey involving students, data was collected regarding the use of (Artificial Intelligence/AI) in the learning process and its impact on the understanding and application of Pancasila values. The results of the study show that the use of (Artificial Intelligence/AI), such as learning applications and discussion platforms, increases student motivation and understanding of Pancasila courses. In addition, (Artificial Intelligence/AI) also facilitates better interaction between lecturers and students, as well as supporting more interactive learning methods. These findings indicate that integration (Artificial Intelligence/AI) in Pancasila learning can strengthen the understanding and application of the country’s basic values in the modern context.